Federal Taxes on Estates, Trusts, and Gifts (Book). - Toner, James V. (The Accounting Review, 1937)
Reviews the book "Federal Taxes on Estates, Trusts and Gifts, 1936-1937," by R.H. Montgomery and Roswell Magill.